Women’s Marriage Age Matters for Public Health: A Review of the Broader Health and Social Implications in South Asia - Marphatia, Akanksha A.; Ambale, Gabriel S.; Reid, Alice M. (Frontiers in Public Health, 2017)
In many traditional societies, women’s age at marriage acts simultaneously as a gateway to new family roles and the likelihood of producing offspring. However, inadequate attention has previously been given to the broader health and social implications of variability in women’s marriage age for public health. Biomedical scientists have primarily been concerned with whether the onset of reproduction occurs before the woman is adequately able to nurture her offspring and maintain her own health. Social scientists have argued that early marriage prevents women from attaining their rightful education, accessing employment and training opportunities, developing social relationships with peers, and participating in civic life. The aim of this review article is to provide comprehensive research evidence on why women’s marriage age, independent of age at first childbirth, is a crucial issue for public health. It focuses on data from four South Asian countries, Bangladesh, India, Nepal, and Pakistan, in which marriage is near universal and where a large proportion of women still marry below the United Nations prescribed minimum marriage age of 18 years. Using an integrative perspective, we provide a comprehensive synthesis of the physiological, bio-demographic, and socio-environmental drivers of variable marriage age. We describe the adverse health consequences to mothers and to their offspring of an early age at marriage and of childbearing, which include malnutrition and high rates of morbidity and mortality. We also highlight the complex association of marriage age, educational attainment, and low societal status of women, all of which generate major public health impact. Studies consistently find a public health dividend of increased girls’ education for maternal and child nutritional status and health outcomes. Paradoxically, recent relative increases in girls’ educational attainment across South Asia have had limited success in delaying marriage age. This evidence suggests that in order for public health initiatives to maximize the health of women and their offspring, they must first address the factors that shape the age at which women marry.